Mutations of the Transporter Proteins GlpT and UhpT Confer Fosfomycin Resistance in Staphylococcus aureus - Xu, Su; Fu, Zhuyingjie; Zhou, Ying; Liu, Yang; Xu, Xiaogang; Wang, Minggui (Frontiers in Microbiology, 2017)
With the increasing spread of methicillin-resistant Staphylococcus aureus worldwide, fosfomycin has begun to be used more often, either alone or in combination with other antibiotics, for treating methicillin-resistant S. aureus infections, resulting in the emergence of fosfomycin-resistant strains. Fosfomycin resistance is reported to be mediated by fosfomycin-modifying enzymes (FosA, FosB, FosC, and FosX) and mutations of the target enzyme MurA or the membrane transporter proteins UhpT and GlpT. Our previous studies indicated that the fos genes might not the major fosfomycin resistance mechanism in S. aureus, whereas mutations of glpT and uhpT seemed to be more related to fosfomycin resistance. However, the precise role of these two genes in S. aureus fosfomycin resistance remains unclear. The aim of the present study was to investigate the role of glpT and uhpT in S. aureus fosfomycin resistance. Homologous recombination was used to knockout the uhpT and glpT genes in S. aureus Newman. Gene complementation was generated by the plasmid pRB473 carrying these two genes. The fosfomycin minimal inhibitory concentration (MIC) of the strains was measured by the E-test to observe the influence of gene deletion on antibiotic susceptibility. In addition, growth curves were constructed to determine whether the mutations have a significant influence on bacterial growth. Deletion of uhpT, glpT, and both of them led to increased fosfomycin MIC 0.5 μg/ml to 32 μg/ml, 4 μg/ml, and >1024 μg/ml, respectively. By complementing uhpT and glpT into the deletion mutants, the fosfomycin MIC decreased from 32 to 0.5 μg/ml and from 4 to 0.25 μg/ml, respectively. Moreover, the transporter gene-deleted strains showed no obvious difference in growth curves compared to the parental strain. In summary, our study strongly suggests that mutations of uhpT and glpT lead to fosfomycin resistance in S. aureus, and that uhpT mutation may play a more important role. The high resistance and low biological fitness cost resulting from uhpT and glpT deletion suggest that these strains might have an evolutionary advantage in a fosfomycin-rich clinical situation, which should be closely monitored.